HUBUNGAN INDEKS MASSA TUBUH DAN RIWAYAT PREEKLAMPSIA SEBELUMNYA DENGAN KEJADIAN PREEKLAMPSIA DI KLINIK PRATAMA UMMI TALANGO - Eny Susanti (JURNAL ILMIAH OBSGIN : Jurnal Ilmiah Ilmu Kebidanan & Kandungan P-ISSN : 1979-3340 e-ISSN : 2685-7987, 2021)
Every Pragnancy always has risk of preeclampsia, according to a preliminary study showing that there is still 11% of preeclampsia incidence at Pratama Ummi Talango Clinic. This study aims to analyze the correlation between body mass index and previous preeclampsia history with the incidence of preeclampsia in Pratama Ummi Talango Clinic. This research is a kind of analytic research with cros sectional design. In this study the independent variable are body mass index and previous preeclampsia history, the dependent variable is the incidence of preeclampsia. The sample is pregnant mother of trimester II and III from January until Pebruary 2021 composed of 46 respondents. The sampling technique which used probability sampling with simple random sampling. Data analysis using statistical test of Lambda and Chi Square with significant level 0,05. The results showed nearly half of pregnant women had an obese body mass index of (43,48%), had a history of preeclampsia (58,70%), and preeclampsia (67,40%). From statistical tests for body mass index and preeclampsia obtained P = 0,003 <a = 0,05 stating that there was correlation of body mass index to the incidence of preeclampsia. Statistical tests for previous preeclampsia history and preeclampsia obtained P = 0,000 <a = 0,05 stating that there is a history of preeclampsia correlation with the incidence of preeclampsia. Efforts that can be done for primary prevention of pregnant women with preeclampsia is to know the group of high risk mothers and obstetric interventions, secondary preventation by early detection of symptoms and early treatment